Faktor-Faktor Kinerja Keuangan Pemda Di Bakorwil Madiun - Mintarti Indartini; Nurharibnnu Wibisono (JAMER : Jurnal Akuntansi Merdeka, 2021)
Its research intend  to determine whether local revenue (PAD), balancing funds (DP), & capital goods expenditures (BM) to the financial performance (KKPD) from city/district in Regional Coordination Agency (Bakorwil) Madiun, East Java, Indonesia partially and simultaneously. The purposive sampling method used forMadiun Regency, Magetan Regency, Ngawi Regency, Ponorogo Regency, and Madiun City  for 5 years (2014-2019). The regression analysis used with SPSS program. This study conclude (1) local-generated revenue has no impact on the financial performance from districts/city at Bakorwil Madiun; (2) Balancing funds influence the financial performance from districts/city at Bakorwil Madiun; (3) Capital expenditures influence the financial performance of districts/city at Bakorwil Madiun; (4) Generally, local revenue, balancing funds, & capital expenditures have an impact to the financial performance of city/districts in Bakorwil Madiun.